2000
DOI: 10.1136/jmg.37.4.287
|View full text |Cite
|
Sign up to set email alerts
|

An unbalanced submicroscopic translocation t(8;16)(q24.3;p13.3)pat associated with tuberous sclerosis complex, adult polycystic kidney disease, and hypomelanosis of Ito

Abstract: We report on a familial submicroscopic translocation involving chromosomes 8 and 16. The proband of the family had a clinical picture suggestive of a large deletion in the chromosome 16p13.3 area, as he was aVected with tuberous sclerosis complex (TSC) and had thalassaemia trait, and his half brother, who also had TSC, may have suVered additionally from polycystic kidney disease (PKD). FISH studies provided evidence for a familial translocation t(8;16)(q24.3;p13.3) with an unbalanced form in the proband and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
3

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 16 publications
1
30
1
3
Order By: Relevance
“…Subsequent FISH analysis of several BACs revealed a far more complex karyotype, with subtelomeric rearrangements involving 16p, 17p, and 20q, an insertion of approximately 9 Mb of 16p (16p13.13 to 16p12.2) into 4p16.3, a small reciprocal insertion of 4p16.3 material into 16p, a second small insertion of 16p13.3 into 4p, and a cryptic deletion of 0.8 Mb in 16p13.3. There have been several reports in the literature of deletions in or rearrangements involving 16p13.3, which is a highly gene-rich area (Brook-Carter et al 1994;Brown et al 2000;Eussen et al 2000;Horsley et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent FISH analysis of several BACs revealed a far more complex karyotype, with subtelomeric rearrangements involving 16p, 17p, and 20q, an insertion of approximately 9 Mb of 16p (16p13.13 to 16p12.2) into 4p16.3, a small reciprocal insertion of 4p16.3 material into 16p, a second small insertion of 16p13.3 into 4p, and a cryptic deletion of 0.8 Mb in 16p13.3. There have been several reports in the literature of deletions in or rearrangements involving 16p13.3, which is a highly gene-rich area (Brook-Carter et al 1994;Brown et al 2000;Eussen et al 2000;Horsley et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Her younger sister showed a more or less similar phenotype. Eussen et al 106 reported a boy with a submicroscopic deletion of 16p13.3-pter and duplication of 8q24.3-qter with tuberous sclerosis, adult polycystic kidney disease, and hypomelanosis of Ito. Brown et al 107 reported a newborn with cranial tubers and subcortical renal cysts suggestive of tuberous sclerosis and additional atypical features such as bilateral nasal colobomas of the eyes, inguinal hernias, glandular hypospadias, cryptorchidism, and facial dysmorphism (telecanthus, short palpebral fissures, broad nasal tip, small mouth with thin lips and small chin) caused by a der(16)t(16;19)(p13.3;p13.3).…”
Section: Qmentioning
confidence: 99%
“…14,15 For DGGE, primers were designed using the Ingeny DGGE Primer Design program (primer sequences available upon request), and pooled PCR products were run on urea/formamide denaturing gradient polyacrylamide gels at 601C for 17 h (Ingeny phorU DGGE system). SSCP was performed on 50% of the patients and DGGE on 75% of the cohort.…”
Section: Patientsmentioning
confidence: 99%